Perancangan Dan Pembuatan Alat Home Electricity Based Home Appliance Controller Berbasis Internet of Things - Ibnu Alfannizar; Yusnita Rahayu (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Currently the increasing of electricity bill become hot topic in Indonesia society. The increasing of electricity bills is due to the uncontrolled usage of home appliances. In addition, the uncontrolled usage of appliance will also cause a fire. One of the alternative solution to over come by deploying a remotely control system for home appliances. This paper purpose a home automation control system design prototyping. This design system is expected comply to Internet of Things (IoT) system. The system consists of hardware and software. The hardware consists of arduino and esp8266. The testing scenario is excuted as the following condition depend an internet for traffic and looping process of and vary of router distance. Conducted three tests based on the distance of the device to the router is specified as follow 30 cm, 5 m and 10 m, respectively. Based on the measurement result, the first test provides 1.93-4.20 seconds of data transmission time. The second test is 2.05-5.20 seconds and the third test is 4.74-8.51 seconds. These results are slightly higher than previous study with only 2-6 seconds. However, this system has ability to receive 100% data compared to other that is only 91.7%.Keyword :Internet of Things, Home Applianced Controller, Control System